Impact of Installing Lightning Arresters on Low Voltage Networks in Areas with High Lightning Incidence per Kilometer - Galvez Millan, Samuel Gandy (2025)
The concession area of Sociedad Eléctrica del Sur Oeste S.A. (SEAL) faces a significant challenge due to the high incidence of atmospheric discharges, ranging from 12 to 30 lightning strikes per square kilometer annually. These discharges result in critical failures in transformers and electrical networks. Current medium - voltage protections are insufficient to effectively mitigate electrical surges that damage secondary windings, leading to increased maintenance costs, service interruptions, and reduced system reliability. The presented article addressed these shortcomings through the implementation of Surge Protective Devices (SPDs), a technology already validated in Europe and Brazil. In critical areas such as Chuquibamba, Valle del Colca, Chococo, Orcopampa, and Huancarama, 1,300 SPDs were installed, distributed across three - phase and single - phase networks. The results demonstrated a significant reduction in failures, preservation of transformers, and low implementation costs — approximately $89.22 per three - phase SED and $44.61 per single - phase SED — totaling an investment of $28,119.00, which significantly reduces losses caused by the problem. Financial analysis confirmed the project’s profitability, with an Internal Rate of Return (IRR) of 14.9%, a Net Present Value (NPV) of $61,298.84, and a payback period of seven years. This viable and effective model reinforces the company’s commitment to innovation and energy efficiency, setting a precedent for expansion into other critical areas.